Prevalence and Associated Factors of Erectile Dysfunction among Married Men in Vietnam - Van Vo, Thang; Hoang, Hue Dinh; Thanh Nguyen, Nhan Phuc (Frontiers in Public Health, 2017)
Background Sexuality is an essential part of life; however, erectile dysfunction (ED) has been one of the most common complaints among men with sexual health issues all over the world. ED includes dysfunction in erection and penile erectile pain. In Vietnam, ED is a subject a not readily discussed. Thus, relatively little is known about ED among Vietnamese men. Aims To identify the prevalence of ED and its associated variables and the need for treatment of ED among married men in Vietnam. Methods This was a cross-sectional study. A total sample size included 746 married men, aged 20–60 years, living in four representative wards of the Hue City and randomly selected by systematic sampling methods. Respondents completed a self-reported questionnaire. The International Index of Erectile Function (IIEF-5) scale was used to determine ED severity, and the Depression Anxiety Stress Scales (DASS-21) was used to measure depression, anxiety, and stress. Quality of life was assessed using the WHO Quality of Life score (WHOQoL). A multivariate logistic regression model was used to determine the relationships between independent variables and ED. Results Mean age of married men was 44.3 ± 8.7. Two-thirds (66.9%) of respondents experienced ED symptoms. In terms of severity, 40.8% reported mild ED; 20.3% mild–moderate ED; 5.0% moderate ED; and 0.8% severe ED. Depression, anxiety, and stress problems were 5.0, 3.6, and 2.8%, respectively. One-third (33.1%) of the respondents reported having low quality of life, and 32.6% reported having medium quality of life. The vast majority (86.9%) had consensual sex with their wives/partners. Variables associated with increased IIEF-5 score were increased WHOQoL score, increased body mass index (BMI), religion, and no consumption of alcohol. Increasing age, disease history, increased anxiety, and no consensual sex with their wife/partner were associated with a lower IIEF-5 score. If experiencing ED, 55.5% would seek help from medical doctors, 55.1% discussed it with their wives/partners, and 23.1% turned to their friends for help. Conclusion The prevalence of ED was high, although only 5.8% experienced moderate to severe ED. The key factors associated with ED were age, religion, disease history, BMI, alcohol consumption, anxiety, quality of life, and consensual sex with their wives/partners. Sexual health education should be more specifically targeted for men, including the provision of local sexual health-care services for men.